Climate change meets trade in promoting green growth: potential conflicts and synergies - ZhongXiang Zhang (Fondazione Eni Enrico Mattei (FEEM), 2010)
To date, border adjustment measures in the form of emissions allowance requirements (EAR) under the U.S. proposed cap-and-trade regime are the most concrete unilateral trade measure put forward to level the carbon playing field. If improperly implemented, such measures could disturb the world trade order and trigger a trade war. Because of these potentially far-reaching impacts, this paper focuses on this type of unilateral border adjustment, which requires importers to acquire and surrender emissions allowances corresponding to the embedded carbon contents in their goods from countries that have not takenclimate actions comparable to that of home country. This discussion is mainly on the legality of unilateral EAR under the WTO rules. Given that the inclusionof border carbon adjustment measures is widely considered essential to secure passage of any U.S. legislation capping its greenhouse gas emissions, the paperargues that, on the U.S. side, in designing such trade measures, WTO rules need to be carefully scrutinised, and efforts need to be made early on to ensure that the proposed measures comply with them. After all, a conflict between the trade and climate regimes, if it breaks out, helps neither trade nor the global climate. The U.S. needs to explore, with its trading partners, cooperative sectoral approaches to advancing low-carbon technologies and/or concerted mitigation efforts in a given sector at an international level. Moreover, to increase the prospects for a successful WTO defence of the Waxman-Markey type of border adjustment provision, there should be: 1) a period of good faith efforts to reach agreements among the countries concerned before imposing such trade measures; 2) consideration of alternatives to trade provisions that could be reasonably expected to fulfill the same function but are not inconsistent or less inconsistent with the relevant WTO provisions; and 3) trade provisions that can refer to the designated special international reserve allowance pool, but should allow importers to submit equivalent emission reduction units that are recognized by international treaties to cover the carbon contents of imported products. The paper concludes by arguing that the major developing countries being targeted by such border carbon adjustment measures should make the best use of the forums provided under the United Nations Framework Convention on Climate Change and its Kyoto Protocol to effectively deal with the proposed border adjustment measures to their advantage.
Keywords: F18; Q48; Q54; Q56; Q58; 330; Post-2012 climate negotiations; Border carbon adjustments; Carbon tariffs; Emissions allowance requirements; Cap-and-trade regime; Lieberman-Warner bill; Waxman-Markey bill; World Trade Organization; Kyoto Protocol; Developing countries; United States; Internationale Umweltpolitik; Klimaschutz; Emissionsrechte; Emissionshandel; Border Tax Adjustment; USA; Entwicklungsländer